The Influence Of Problem-Based Learning Strategies And Learning Styles On Mathematics Learning Outcomes Class V Students Of State Private Primary School Datuk Fifty Batubara District - Elvi Nurhayati Selian; Efendi Napitupulu; Tian Abdul Aziz (Jurnal Info Sains : Informatika dan Sains, 2024)
The research aims to determine the differences in student learning outcomes taught using problem-based learning strategies with expository learning in class V of SD Negeri Datuk Limapuluh District, Batubara Regency. Differences in learning outcomes of students who have visual, kinesthetic and auditory learning styles in class V of SD Negeri Datuk Limapuluh District, Batubara Regency. The interaction between learning strategies and learning styles on student learning outcomes. Based on the results of the ANOVA test, the value obtained was sig=0.036<sig.0.05, thus proving that there was an interaction between learning strategies and learning styles on student learning outcomes. The sample was determined as 60 people consisting of 2 (two) classes. The research design used in this research is experimental. There are differences in learning outcomes for students who have visual, kinesthetic and auditory learning styles in class V of SD Negeri Datuk Limapuluh District, Batubara Regency. There is an interaction between learning strategies and learning styles on student learning outcomes. Based on the results of the ANOVA test, the value obtained was sig=0.036<sig.0.05, thus proving that there was an interaction between learning strategies and learning styles on student learning outcomes.